Social media influencer in advertising: the role of attractiveness, expertise and trustworthiness - Brahim Chekima; Fatima Zohra Chekima; Azaze Azizi Abdul Adis (The Asian Institute of Research, 2020)
The cosmetic industry has shown rapid growth worldwide and is seen as a profitable business yet highly competitive. A popular grab-attention strategy being adopted worldwide by the brand manufacturers is celebrity endorsement to improve the effectiveness of the advertisement. Despite its popularity, companies increasingly abandoning it in favor of social media influencers due to the popularity of social media and online stores. However, the effectiveness of this new way of communication using an influencer is not well understood. To address this gap, this research investigated the influence of social media influencer credibility (attractiveness, trustworthiness, and expertise) on advertising effectiveness (attitude toward the product, attitude toward the advertisement, and purchase intention to ensure if it is suitable to hire a social media influencer to advertise cosmetic products in Malaysia over a celebrity. The finding can serve as a reference to help cosmetic products marketers to develop effective ads using source credibility to communicate with their customers and stand out from the surrounding media clutter.